Manganese dioxide-vulcan carbon@silver nanocomposites for the application of highly sensitive and selective hydrazine sensors - Babu, K.J.; Zahoor, A.; Nahm, K.S.; Aziz, M.A.; Periasamy, V.; Kumar, G.G. (Royal Society of Chemistry, 2016)
Manganese dioxide (MnO2)-vulcan carbon (VC)@silver (Ag) (core@shell) nanocomposites were synthesized through a simple wet chemical method without using hazardous organic reagents, polymeric micelles, templates or catalysts. The synthesized MnO2-VC@Ag exhibited a MnO2-VC core and Ag shell, and the thickness of shell was found to be 23 nm. The obtained diffraction patterns confirmed that the prepared nanocomposite consists of tetragonal and face-centred cubic structures of MnO2 and Ag nanostructures, respectively. Cyclic voltammetry and amperometric techniques were adopted to electrochemically characterize the MnO2-VC@Ag nanospheres for hydrazine oxidation in phosphate buffer solution. Under the optimized conditions, the fabricated sensor exhibited a good electrochemical performance toward hydrazine oxidation, offering a broad linearity of 0.1 to 350 μM, with a relatively low detection limit of 100 nM and a high sensitivity of 0.33 μA μM-1 cm-2. In addition, anti-interference properties, good reproducibility, long term performance, good repeatability and real sample analysis were achieved for the constructed sensor, owing to the synergetic effects of the Ag and MnO2-VC nanostructures. The aforesaid attractive analytical performance and facile preparation of the MnO2-VC@Ag core-shell nanospheres are new features for electrocatalytic materials and may hold promise for the design and development of effective hydrazine sensors.